Engaging with social work : a critical introduction - Morley, Christine, ....-; Ablett, Phillip, ....-; Macfarlane, Selma, ....- (Cambridge : Cambridge University Press, 2016)
This book provides a comprehensive introduction to the diverse and contested world of social work. It explores the key concepts and theoretical frameworks underpinning contemporary social work practice, as well as relevant professional skills and strategies from a critical perspective. In a rapidly changing world, it locates critical social work as a part of broader and ongoing struggles for social justice and human rights. Readers are encouraged to think about what social work is or should be, and what sort of social worker they would like to become. The book covers a broad range of topics, including the history and development of social work as a profession, values and ethics, theories for practice, and the fields and context of practice. Definitions of key terms, reflective exercises and case studies are integrated throughout the text. Written by a diverse team of experienced educators, this is a stimulating, rigorous and student-friendly resource.